Penggunaan Metode Free Settler Pada Proses Perhitungan Ukuran Butiran Magnesium Karbonat Menggunakan Persamaan Stokes [Study of Magnesium Carbonate Particle Size Measurement from Carbonation Process with Free Settler Method] - Priyanti, Ayu Dwi (Jurnal Metalurgi, 2019)
Particle size measurement with the free settler method is the most practical and straightforward method. The principle of this method is the presence of gravity that is opposite with buoyancy due to the pressure between liquid and solid. This paper explains the use of the free settler method as a reference in the magnesium carbonate particle size measurement method. In this research, nano magnesium carbonate was made by heating magnesium bicarbonate solution using ultrasonic wave and hot plate. The optimum result of nano magnesium carbonate using ultrasonic heating process with 30% amplitude for 35 minutes by stokes method is 0.491 µm – 1.072 µm, while using the PSA (particle size analysis) is 0.451 µm – 2.617 µm. It shows that although the particle size measurement with those analysis methods has different results, they still have intersecting size range. It also can be seen that the grain size will be reduced when an ultrasonic wave is added. In this work, the free settler method can be used as a preliminary method to predict the particle size of nanomaterial should a particle size analyzer (PSA) is not available.